Indicators of Regional Development Using Differentiation Characteristics - Sergei A. Aivazian; Mikhail Yu. Afanasiev; Alexander V. Kudrov (Montenegrin Journal of Economics)
On the example of two directions - "production of goods and services" and "welfare", it is developed a methodology for analyzing the interrelationship between various directions of regional development. The novelty of the results is determined by the fact that the direction indicators are constructed using a common basis formed using the characteristics of regional differentiation obtained from theoretically based models. The index for each direction, constructed in the basis, is maximally correlated with the index formed for the corresponding group of indicators. It is shown that for the considered two directions, the basis ensures higher consistency of the indices and ranks of the regions than the first principal components constructed for each group of the indicators separately. The advantage of the approach is that the indices for different directions based on the basis allow a general interpretation in terms of the differentiation characteristics and allow one to assess the change in the level of socio-economic development of the region when these characteristics change. The presented results confirm the significance of the influence of technical efficiency on the indices of regional development and its significance in the indicator composition for the direction of "welfare".